2010
DOI: 10.1063/1.3428910
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of SiPM Photosensors in the Presence of Magnetic Fields

Abstract: Abstract:The Multi Pixel Photon Counter (MPPC) or Silicon Photomultiplier (SiPM) consists of an array of Geiger-mode photodiodes (microcells). It is a promising device for PET thanks to its high photon detection efficiency (PDE) and immunity to high magnetic fields. It is also very easy to use, with simple electronic read-out, high gain and small size. In this work we evaluate the performance of three 1 x 1 mm 2 SiPM and one 2 x 2 SiPMs array (6 x 6 mm 2 of active area). We examine the dependence of the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…We then compared the performance of each photodetector using several 235 U enrichment standards by measuring the energy resolution of the 235 U-186 keV and 238 U-1001 keV gamma peaks, as well as the enrichment predictive capability. This study did not include investigation of magnetic field effects but this has been reported on in other experiments [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…We then compared the performance of each photodetector using several 235 U enrichment standards by measuring the energy resolution of the 235 U-186 keV and 238 U-1001 keV gamma peaks, as well as the enrichment predictive capability. This study did not include investigation of magnetic field effects but this has been reported on in other experiments [8][9][10].…”
Section: Introductionmentioning
confidence: 99%